2003
DOI: 10.1207/s1532690xci2102_02
|View full text |Cite
|
Sign up to set email alerts
|

Point and Click or Grab and Heft: Comparing the Influence of Physical and Virtual Instructional Materials on Elementary School Students' Ability to Design Experiments

Abstract: The widespread availability of computers in elementary schools makes them an appealing option for presenting instructional materials in laboratory science. However, there are neither theoretical nor empirical grounds for predicting whether virtual or physical presentation of instructional materials will be more effective. The definition of "active manipulation" is poorly specified and there are few studies that directly compare the two approaches unaccompanied by other potential confounds. In this study, 4th-a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
152
1
15

Year Published

2005
2005
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 198 publications
(199 citation statements)
references
References 26 publications
16
152
1
15
Order By: Relevance
“…The study extends the work of Triona and Klahr (2003) in several important ways. Triona and Klahr found that virtual and physical materials were equally effective in producing significant gains in children's ability to design unconfounded experiments and to learn about the properties of springs from those experiments.…”
Section: Designing and Testing Physical And Virtual Mousetrap Carssupporting
confidence: 55%
See 4 more Smart Citations
“…The study extends the work of Triona and Klahr (2003) in several important ways. Triona and Klahr found that virtual and physical materials were equally effective in producing significant gains in children's ability to design unconfounded experiments and to learn about the properties of springs from those experiments.…”
Section: Designing and Testing Physical And Virtual Mousetrap Carssupporting
confidence: 55%
“…Further discussion of this issue can be found in a study by Triona and Klahr (2003) and in Clements' (1999) review of physical versus computer manipulatives in early mathematics instruction. The study to be described in this paper examines the instructional effects of physical versus virtual materials while holding constant all other likely causal factors.…”
Section: Instructional Materials: Physical or Virtual?mentioning
confidence: 99%
See 3 more Smart Citations